2018
DOI: 10.1080/14767058.2018.1458835
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative noninvasive cardiac output monitoring in parturients undergoing cesarean delivery with spinal anesthesia and prophylactic phenylephrine drip: a prospective observational cohort study

Abstract: Significant hemodynamic changes were documented at all time points both intraoperatively and postoperatively with the most significant changes occurring 1 hour postoperatively. Further studies need to be performed to discover hemodynamic changes of spinal anesthesia and PPI in different parturient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
1
4
0
2
Order By: Relevance
“…Phenylephrine is known to cause a dose-dependent decrease in cardiac output. 19 In a previous study performed in our institution, measuring cardiac output at different time points during CD performed under spinal anesthesia with a prophylactic phenylephrine infusion, the pattern of changes in stroke volume at different time points corresponded to the changes in mean frontal lobe ScO 2 seen in the current study. 19 In the study comparing ephedrine and phenylephrine boluses, phenylephrine decreased cardiac output while ephedrine maintained it; and there Cerebral hypoperfusion threshold = absolute decrease of cerebral saturation <50% or decrease more than 20% from baseline.…”
Section: Discussionsupporting
confidence: 71%
“…Phenylephrine is known to cause a dose-dependent decrease in cardiac output. 19 In a previous study performed in our institution, measuring cardiac output at different time points during CD performed under spinal anesthesia with a prophylactic phenylephrine infusion, the pattern of changes in stroke volume at different time points corresponded to the changes in mean frontal lobe ScO 2 seen in the current study. 19 In the study comparing ephedrine and phenylephrine boluses, phenylephrine decreased cardiac output while ephedrine maintained it; and there Cerebral hypoperfusion threshold = absolute decrease of cerebral saturation <50% or decrease more than 20% from baseline.…”
Section: Discussionsupporting
confidence: 71%
“…CO and SVR changes after spinal anesthesia are still controversial. Previous studies have reported that CO increases significantly immediately after spinal anesthesia, followed by a significant reduction in CO subsequent to the administration of vasoconstriction drugs (15,16). A rapid and profound reduction in SVR after spinal anesthesia often precedes the reduction in MAP (17).…”
Section: Discussionmentioning
confidence: 95%
“…Частота развития артериальной гипотонии у беременных в ходе применения нейроаксиальных методов обезболивания может составлять от 80-90 % [22][23][24][25]. Механизм развития данного осложнения связан непосредственно с артериальной дилатацией и снижением системного сосудистого кровотока, что первоначально обусловлено развитием симпатической блокады.…”
Section: Impact Of Anesttesia Methods On Foetus Conditionunclassified